Conductive adhesive sheet

A conductive adhesive sheet with a specific composition and resistance range addresses the limitations of conventional absorbers by effectively absorbing millimeter waves, enhancing noise reduction and safety in electronic devices.

JP2025015579APending Publication Date: 2025-01-30MAXELL LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024196824
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-11-04
Filing Date
2024-11-11
Publication Date
2025-01-30

AI Technical Summary

Technical Problem

Conventional electromagnetic wave absorbers, such as the λ/4-type absorbers, are ineffective in reducing noise and interference from millimeter waves due to high surface resistance and require additional layers that make them unsuitable for direct application on electronic devices, and existing conductive adhesive sheets do not provide adequate electromagnetic wave absorption in the 1 to 30 GHz microwave range.

Method used

A conductive adhesive sheet composed of a substrate, conductive layer, migration prevention layer, and adhesive layer, using flame-retardant materials, conductive polymers, and carbon materials, with a surface electric resistance of 50 to 200Ω/square, providing electromagnetic wave absorption from 1 to 30 GHz microwaves.

Benefits of technology

The conductive adhesive sheet effectively absorbs electromagnetic waves in the millimeter wave band, is flexible, and safe for electronic devices, offering improved noise reduction and heat management.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025015579000001_ABST
    Figure 2025015579000001_ABST
Patent Text Reader

Abstract

To provide a conductive adhesive sheet which is usable while being stuck to an electronic device, has electromagnetic wave absorption performance in a band width of 1 to 30 GHz from a microwave to a millimeter wave, can cope with heat generation trouble of an electronic device, and has high safety.SOLUTION: A conductive adhesive sheet has a base material, a conductive layer, a transition prevention layer, and an adhesive layer in this order, wherein the base material is composed of a flame-retardant material, the conductive layer contains a conductive material and a binder, the conductive material contains at least one selected from a conductive polymer material and a carbon material, the transition prevention layer is composed of a resin material, the adhesive layer contains an adhesive and a flame retardant, a surface electric resistance value on the base material side is 50 to 200 Ω / sq., and total thickness is 50 to 200 μm.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present application relates to a conductive adhesive sheet that absorbs electromagnetic waves in the microwave to millimeter wave bands. [Background technology]

[0002] With the development of wireless communication technology, typified by mobile phones, various devices and sensors are being connected to networks wirelessly. In the medical field, devices are becoming cordless from the perspective of infection prevention, and medical devices are beginning to be connected wirelessly. These communications require high speed and large capacity over relatively short distances, and the frequencies used are high. With the increase in devices using such high frequencies, the risk of malfunctions in electronic devices and communications due to malfunctions caused by noise generated by the devices and interference with the electromagnetic waves used is increasing. Furthermore, in recent years, millimeter wave radars have also begun to be installed in vehicles to prevent automobile collision accidents. Malfunctions in these medical and automotive devices can affect human lives, so malfunctions must not occur. Therefore, there is an increasing need to apply electromagnetic wave absorbers to circuit elements and transmission lines that emit and receive electromagnetic waves from the microwave to millimeter wave bands as a measure to prevent malfunctions caused by noise and interference in devices, or as a measure for so-called EMC (Electromagnetic Compatibility).

[0003] In order to suppress high frequency noise, the electromagnetic wave absorbing sheet utilizing the magnetic loss of the magnetic material that has been used conventionally is not effective. For this reason, a λ / 4 type electromagnetic wave absorber has been proposed (Patent Document 1). However, since the λ / 4 type electromagnetic wave absorber proposed in Patent Document 1 needs to have a reflective layer, a dielectric layer, and a low resistance layer, it is difficult to use the λ / 4 type electromagnetic wave absorber by attaching it to an electronic device that is desired to prevent the influence of noise with an adhesive or the like. In addition, Patent Document 1 describes a precursor that does not have a reflective layer and a dielectric layer before forming a λ / 4 type electromagnetic wave absorber, and a laminate for a radio wave absorber that has a sheet base material, a low resistance layer, a barrier layer, and an adhesive layer in this order, but the surface resistance value of the low resistance layer is large at 300 to 450 Ω / square, and even if the laminate for an electromagnetic wave absorber is used as it is as an electromagnetic wave absorbing sheet, it is not possible to improve the electromagnetic wave absorbing performance in the microwave to millimeter wave band of 1 to 30 GHz.

[0004] Furthermore, Patent Document 2 is a prior art document related to the conductive adhesive sheet of the present application. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2006-120836 A [Patent Document 2] JP 2017-54734 A Summary of the Invention [Problem to be solved by the invention]

[0006] The present application solves the above problems by providing a highly safe conductive adhesive sheet that can be attached to electronic devices where it is desired to prevent the effects of noise with an adhesive or the like, has electromagnetic wave absorption performance in the microwave to millimeter wave bands of 1 to 30 GHz, and can also deal with heat generation problems in electronic devices. [Means for solving the problem]

[0007] The conductive adhesive sheet of the present application comprises, in this order, a substrate, a conductive layer, a migration prevention layer, and an adhesive layer, the substrate being composed of a flame-retardant material, the conductive layer comprising a conductive material and a binder, the conductive material comprising at least one material selected from a conductive polymer material and a carbon material, the migration prevention layer being composed of a resin material, the adhesive layer comprising an adhesive and a flame retardant, and characterized in that the surface electrical resistance value on the substrate side is 50 to 200 Ω / square, and the total thickness is 50 to 200 μm. Effect of the Invention

[0008] According to the present application, it is possible to provide a highly safe conductive adhesive sheet that can be attached to electronic devices, has electromagnetic wave absorption performance in the microwave to millimeter wave band of 1 to 30 GHz, and can also deal with heat generation problems in electronic devices. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of a conductive adhesive sheet according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] (Conductive adhesive sheet) An embodiment of the conductive adhesive sheet of the present application will be described. The conductive adhesive sheet of this embodiment includes a substrate, a conductive layer, a migration prevention layer, and an adhesive layer in this order, the substrate is made of a flame-retardant material, the conductive layer includes a conductive material and a binder, the conductive material includes at least one selected from a conductive polymer material and a carbon material, the migration prevention layer is made of a resin material, the adhesive layer includes an adhesive and a flame retardant, the surface electrical resistance value on the substrate side is 50 to 200 Ω / square, and the total thickness is 50 to 200 μm.

[0011] In the conductive adhesive sheet of the present application, the conductive layer contains a conductive material, so that the conductive layer has an electromagnetic wave absorbing function and can absorb electromagnetic waves of higher frequencies than conventional electromagnetic wave absorbing layers made of magnetic materials. In addition, since the conductive layer contains a binder and the migration prevention layer is made of a resin material, flexibility can be imparted to the entire conductive adhesive sheet, making it easy to make the conductive adhesive sheet conform to the surface shape of the electronic device to which it is attached. Furthermore, since the base material is made of a flame-retardant material and the adhesive layer contains a flame retardant, when the conductive adhesive sheet is attached to an electronic device to which it is desired to prevent the influence of noise, it is possible to provide a conductive adhesive sheet with high safety, which can deal with heat generation problems of the electronic device.

[0012] If the surface electrical resistance value of the substrate side of the conductive adhesive sheet is too low or too high, it becomes difficult to exhibit the absorption performance for electromagnetic waves of a specific frequency. In the conductive adhesive sheet to be used by attaching it to an electronic device that needs to be protected from the influence of noise with an adhesive or the like, the surface electrical resistance value of the substrate side of the conductive adhesive sheet suitable for exhibiting the electromagnetic wave absorption performance in the microwave to millimeter wave band of 1 to 30 GHz is 50 to 200 Ω / square, and optimally 80 to 150 Ω / square.

[0013] The conductive adhesive sheet of this embodiment will be described below with reference to the drawings. Fig. 1 is a schematic cross-sectional view showing an example of the conductive adhesive sheet of this embodiment. In Fig. 1, the conductive adhesive sheet 10 includes a substrate 11, a conductive layer 12 disposed on the substrate 11, a migration prevention layer 13 disposed on the conductive layer 12, and an adhesive layer 14 disposed on the migration prevention layer 13.

[0014] Hereinafter, each of the components of the conductive adhesive sheet of this embodiment will be described.

[0015] <Base material> The substrate used in the conductive adhesive sheet of this embodiment is made of a flame-retardant material. By making the substrate from a flame-retardant material, it is possible to deal with heat generation problems in electronic devices to which the conductive adhesive sheet is attached, and to provide a highly safe conductive adhesive sheet. The substrate is usually used in the form of a flame-retardant resin film.

[0016] As the flame-retardant material, a flame-retardant resin material or a resin material containing a flame retardant can be used. The flame-retardant resin material is a resin material whose resin itself has flame retardancy, and examples thereof include polyamide (aramid), polyimide, polyphenylene sulfide, and the like. Examples of flame-retardant resin films using the flame-retardant resin material include "Nomex" (registered trademark) manufactured by Teijin DuPont Advanced Paper Co., Ltd., which uses heat-resistant and flame-retardant meta-aramid fibers, "Xenomax" (registered trademark) manufactured by Xenomax Japan Co., Ltd., as a highly heat-resistant polyimide film, "Mictron" (registered trademark) manufactured by Toray Industries, Inc., as a loose aromatic polyamide (aramid) film, and "Torelina" (registered trademark) manufactured by Toray Industries, Inc., as a polyphenylene sulfide film.

[0017] In addition, a resin material containing a flame retardant is a resin material in which a flame retardant is incorporated into a resin that does not have flame retardancy. Examples of flame-retardant resin films using resin materials containing the above-mentioned flame retardant include "Tetoron UF" (product name) manufactured by Toyobo Co., Ltd., "Fumiron" (registered trademark) manufactured by Wako Chemical Co., Ltd., "Dialamy" (registered trademark) manufactured by Mitsubishi Chemical Corporation, "Iupilon" (registered trademark) manufactured by Mitsubishi Engineering Plastics Corporation, and "Sunroid Ecosheet Polyca PHF Series" (product name) manufactured by Sumitomo Bakelite Co., Ltd.

[0018] The thickness of the flame-retardant substrate made of the flame-retardant material is preferably 25 to 180 μm, more preferably 80 to 150 μm. If the thickness is less than 25 μm, the flame retardant standard UL94VTM cannot be satisfied, and the flame retardancy of the substrate cannot be ensured. On the other hand, if the thickness is more than 180 μm, the flame retardancy is not an issue, but the flexibility of the flame-retardant resin film decreases, so that the conformability when attached to electronic components decreases and it becomes difficult to wrap around wiring, etc. If the thickness is 50 μm or more, the flame retardant standard VTM-2 (minimum standard) can be satisfied. Furthermore, if the thickness is 100 μm or more, the flame retardant standard VTM-0, which is stricter than VTM-2, can be satisfied.

[0019] <Conductive layer> The conductive layer used in the conductive adhesive sheet of this embodiment includes a conductive material and a binder, and the conductive material includes at least one selected from a conductive polymer material and a carbon material. By including a conductive material including at least one selected from a conductive polymer material and a carbon material in the conductive layer, the surface electrical resistance value of the substrate side of the conductive adhesive sheet can be set within a range of 50 to 200 Ω / square. By setting the surface electrical resistance value within a range of 50 to 200 Ω / square, the conductive adhesive sheet can be provided with electromagnetic wave absorption performance in the microwave to millimeter wave band of 1 to 30 GHz.

[0020] In addition, the conductive layer contains a binder, which allows the conductive layer to have high hardness and high adhesion to the substrate, and further allows the conductive layer to have a small thickness variation on the substrate, thereby making the surface electrical resistance of the entire conductive layer uniform.

[0021] The thickness of the conductive layer is preferably 0.5 μm or more and 2.0 μm or less. If the thickness of the conductive layer is less than 0.5 μm, the surface electrical resistance of the conductive layer increases, making it difficult to make the surface electrical resistance of the conductive adhesive sheet on the substrate side 200 Ω / square or less. If the thickness of the conductive layer exceeds 2.0 μm, the surface electrical resistance of the conductive adhesive sheet on the substrate side can be made 200 Ω / square or less, but the total thickness of the conductive adhesive sheet increases, reducing the flexibility of the conductive adhesive sheet, reducing the followability when attached to electronic components, and making it difficult to wrap the conductive adhesive sheet around wiring, etc.

[0022] [Conductive polymer materials] As the conductive polymer material, it is preferable to use a polythiophene conductive polymer. The polythiophene conductive polymer is an organic polymer having an electromagnetic wave absorption function in the microwave to millimeter wave band of 1 to 30 GHz, and the main chain is composed of a π-conjugated system. Since it has conductivity and hardly absorbs light in the visible light region, a conductive layer having high transparency can be formed. Therefore, a conductive layer using a polythiophene conductive polymer can be laminated on a transparent substrate to form a conductive adhesive sheet having high light transmittance.

[0023] Examples of the polythiophene-based conductive polymer include poly(thiophene), poly(3-methylthiophene), poly(3-ethylthiophene), poly(3-propylthiophene), poly(3-butylthiophene), poly(3-hexylthiophene), poly(3-heptylthiophene), poly(3-octylthiophene), poly(3-decylthiophene), poly(3-dodecylthiophene), poly(3-octadecylthiophene), poly(3-bromothiophene), poly(3-chlorothiophene), poly (3-iodothiophene), poly(3-cyanothiophene), poly(3-phenylthiophene), poly(3,4-dimethylthiophene), poly(3,4-dibutylthiophene), poly(3-hydroxythiophene), poly(3-methoxythiophene), poly(3-ethoxythiophene), poly(3-butoxythiophene), poly(3-hexyloxythiophene), poly(3-heptyloxythiophene), poly(3-octyloxythiophene), poly(3-decyloxythiophene), poly(3- dodecyloxythiophene), poly(3-octadecyloxythiophene), poly(3,4-dihydroxythiophene), poly(3,4-dimethoxythiophene), poly(3,4-diethoxythiophene), poly(3,4-dipropoxythiophene), poly(3,4-dibutoxythiophene), poly(3,4-dihexyloxythiophene), poly(3,4-diheptyloxythiophene), poly(3,4-dioctyloxythiophene), poly(3,4-didecyloxythiophene), poly(3,4 -didodecyloxythiophene), poly(3,4-ethylenedioxythiophene), poly(3,4-propylenedioxythiophene), poly(3,4-butenedioxythiophene), poly(3-methyl-4-methoxythiophene), poly(3-methyl-4-ethoxythiophene), poly(3-carboxythiophene), poly(3-methyl-4-carboxythiophene), poly(3-methyl-4-carboxyethylthiophene), poly(3-methyl-4-carboxybutylthiophene), and the like.

[0024] The polythiophene-based conductive polymers may be used alone or in combination of two or more kinds.

[0025] In order to increase the electrical conductivity of the polythiophene-based conductive polymer, it is preferable to use a dopant in combination with the polymer, which may be, for example, halogens such as iodine and chlorine, Lewis acids such as BF3 and PF5, protonic acids such as nitric acid and sulfuric acid, transition metals, alkali metals, amino acids, nucleic acids, surfactants, dyes, chloranil, tetracyanoethylene, TCNQ, or the like.

[0026] It is preferable to use a mixture (also called PEDOT / PSS) in which poly(3,4-ethylenedioxythiophene) is used as the polythiophene-based conductive polymer and polystyrenesulfonic acid is used as the dopant.

[0027] The content of the conductive polymer material in the conductive layer is preferably 10 to 40 mass % based on the total solid content. By setting the content within this range, the surface electrical resistance value on the substrate side of the conductive adhesive sheet can be set within the range of 50 to 200 Ω / square, and the conductive adhesive sheet can be endowed with electromagnetic wave absorption performance in the microwave to millimeter wave band of 1 to 30 GHz.

[0028] On the other hand, if the content of the conductive polymer material is less than 10% by mass, it becomes difficult to form a conductive path in the conductive layer, and it becomes difficult to reduce the surface electrical resistance value on the substrate side of the conductive adhesive sheet. Also, if the content exceeds 40% by mass, the effect of reducing the surface electrical resistance value becomes saturated, and the content of the binder in the conductive layer decreases relatively, the strength of the conductive layer decreases, and the adhesion to the substrate and the migration prevention layer described later tends to decrease.

[0029] [Carbon materials] The carbon material is an electromagnetic wave absorbing material having an electromagnetic wave absorbing function in the microwave to millimeter wave band of 1 to 30 GHz, and specific examples thereof include graphite; carbon black (acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, etc.); graphene; carbon nanotubes (single-wall carbon nanotubes, multi-wall carbon nanotubes, branched carbon nanotubes, branched multi-wall carbon nanotubes); carbon fibers, etc.

[0030] As the carbon material, carbon black having an average particle size of 10 to 300 nm is particularly preferable. The carbon black has excellent electrical conductivity and can exhibit an electromagnetic wave absorbing function even when used in small amounts. The average particle size of the carbon black can be measured using a particle size distribution measuring device "LA-920" manufactured by Horiba, Ltd.

[0031] The content of the carbon material in the conductive layer is preferably 30 to 70 mass % based on the total solid content. By setting the content within this range, the surface electrical resistance value on the substrate side of the conductive adhesive sheet can be set within the range of 50 to 200 Ω / square, and the conductive adhesive sheet can be endowed with electromagnetic wave absorption performance in the microwave to millimeter wave band of 1 to 30 GHz.

[0032] On the other hand, if the content of the carbon material is less than 30% by mass, it becomes difficult to form a conductive path in the conductive layer, and it becomes difficult to reduce the surface electrical resistance value on the substrate side of the conductive adhesive sheet. Also, if the content exceeds 70% by mass, the effect of reducing the surface electrical resistance value becomes saturated, and the content of the binder in the conductive layer decreases relatively, the strength of the conductive layer decreases, and the adhesion to the substrate and the migration prevention layer described later tends to decrease.

[0033] [Binder] Examples of the binder that can be used include binders containing fluorine-based resins such as polyvinylidene fluoride resin (PVDF), vinylidene fluoride-acrylic copolymer, and vinylidene fluoride-hexafluoropropylene copolymer; and binders containing polyvinyl alcohol resin, acrylic resin, polyester resin, polycarbonate resin, polyurethane resin, polystyrene resin, polyvinyl chloride resin, polyvinylidene chloride resin, and polyvinyl acetate resin.

[0034] <Adhesive layer> The adhesive layer used in the conductive adhesive sheet of this embodiment contains an adhesive and a flame retardant.

[0035] The thickness of the adhesive layer is preferably 10 to 50 μm, more preferably 15 to 35 μm. If the thickness is less than 10 μm, sufficient adhesive strength may not be obtained. If the thickness exceeds 50 μm, the adhesive effect of the adhesive layer is saturated and the total thickness of the conductive adhesive sheet is increased, so that the flexibility of the conductive adhesive sheet is reduced, the conformability when attached to an electronic component is reduced, and it becomes difficult to wrap the conductive adhesive sheet around wiring, etc.

[0036] [Adhesive] The pressure-sensitive adhesive layer preferably contains an acid-free crosslinking resin as a pressure-sensitive adhesive, which can suppress the change over time in the surface electrical resistance value of the conductive layer under high temperature and high humidity conditions and can prevent corrosion of the adherend.

[0037] The acid-free crosslinking resin is a crosslinked polymer formed by polymerizing a monomer that does not contain an acidic group such as a carboxyl group, a sulfonic acid group, or a phosphoric acid group, and then crosslinking the acid-free polymer with a crosslinking agent. The monomer that does not contain an acidic group contains a functional group such as a hydroxyl group or an amino group in order to carry out a crosslinking reaction with the crosslinking agent. However, the acid-free crosslinking resin means one that does not intentionally have an acidic group, and does not mean that no acidic group is detected at all, and also means that a small amount of acid that is inevitably mixed in during the manufacturing process of the adhesive layer is acceptable.

[0038] As the acid-free polymer having a functional group other than an acidic group used in forming the acid-free crosslinked resin, for example, at least one of acrylic resins, urethane resins, rubber resins, silicone resins, and the like can be used.

[0039] The crosslinking agent for forming the acid-free crosslinked resin is not particularly limited, and may be, for example, an epoxy-based crosslinking agent, an isocyanate-based crosslinking agent, an imine-based crosslinking agent, a metal chelate-based crosslinking agent, a melamine-based crosslinking agent, etc. Among these, it is preferable to use an epoxy-based crosslinking agent, an isocyanate-based crosslinking agent, and a metal chelate-based crosslinking agent. By using an epoxy-based crosslinking agent, an isocyanate-based crosslinking agent, and a metal chelate-based crosslinking agent, crosslinking of an acid-free polymer having a functional group other than an acidic group proceeds even under relatively low temperature conditions such as room temperature.

[0040] [Flame retardant] As the flame retardant, organic flame retardants such as phosphorus-containing compounds and halogen-containing compounds, and inorganic flame retardants such as metal hydroxides and antimony-based compounds can be used. Among these, it is preferable to use phosphorus-containing compounds, which are excellent in both flame retardancy and safety.

[0041] Examples of the phosphorus-containing compound include red phosphorus compounds, phosphoric acid compounds, phosphoric ester compounds, ammonium phosphate compounds, and polymeric compounds obtained by polymerizing these compounds.

[0042] The phosphorus-containing compounds can be used in combination of two or more kinds. Phosphorus-containing compounds include those with high flame retardancy, those with excellent solubility, and those with excellent compatibility with resins and adhesives, depending on the structure. In order to achieve both flame retardancy and adhesion, it is necessary to understand the properties of these phosphorus-containing compounds and use two or more kinds of phosphorus-containing compounds in combination to realize an adhesive layer with better flame retardancy and adhesion. Specifically, in order to achieve excellent flame retardancy, for example, it is better to add a large amount of ammonium polyphosphate. However, if too much ammonium polyphosphate is added, the adhesive layer will have poor adhesion. Therefore, when a large amount of ammonium polyphosphate is added, for example, a phosphoric ester can be further added to achieve both flame retardancy and adhesion. In this way, it is possible to bring out the performance of the adhesive layer to be achieved, such as achieving both flame retardancy and adhesion.

[0043] The content of the phosphorus-containing compound in the adhesive layer (when two or more kinds of phosphorus-containing compounds are used, the total content thereof) is preferably 10 to 60 mass % based on the total solid content, and more preferably 20 to 50 mass %. If the content is less than 10 mass %, the UL94VTM-2 standard of the UL94VTM flame retardancy standard may not be satisfied, and sufficient flame retardancy may not be obtained. If the content exceeds 60 mass %, the amount of adhesive in the adhesive layer becomes relatively small, and therefore the adhesive strength and holding strength of the conductive adhesive sheet to the adherend may not be obtained. That is, when the content is 10 to 60 mass %, the compatibility of flame retardancy, adhesive strength, and holding strength can be more effectively achieved. If the content is 20 to 50 mass %, the compatibility of flame retardancy, adhesive strength, and holding strength can be more effectively achieved.

[0044] [Other ingredients] In order to control the adhesive strength, a tackifier may be added to the adhesive layer as necessary. Examples of the tackifier include rosin resins, terpene resins, terpene phenol resins, synthetic petroleum resins, and hydrogenated resins thereof. In addition, colorants such as dyes and pigments, UV absorbers, inorganic fillers, etc. may be added as necessary.

[0045] <Migration prevention layer> The migration prevention layer used in the conductive adhesive sheet of this embodiment is made of a resin material and is disposed between the conductive layer and the adhesive layer, thereby preventing the flame retardant contained in the adhesive layer and the low molecular weight components of the adhesive from migrating from the adhesive layer to the conductive layer.

[0046] The thickness of the migration prevention layer is preferably 0.1 to 2.0 μm, more preferably 0.3 to 1.0 μm. If the thickness is less than 0.1 μm, the flame retardant contained in the adhesive layer and the low molecular weight components of the adhesive will migrate to the conductive layer over time, resulting in an increase in the surface electrical resistance of the conductive layer, which may make it difficult to maintain the surface electrical resistance of the substrate side of the conductive adhesive sheet at 200 Ω / square or less. If the thickness is more than 2.0 μm, the overall thickness of the conductive adhesive sheet will be large, resulting in a decrease in the flexibility of the conductive adhesive sheet, which may decrease the followability when attached to an electronic component, or make it difficult to wrap the conductive adhesive sheet around wiring or the like.

[0047] [Resin material] Examples of the resin materials include acrylic resins, polyester resins, polyurethane resins, polystyrene resins, etc., and polymer compounds having highly polar functional groups such as hydroxyl groups have excellent gas barrier properties. In particular, polymers with a high hydroxyl group content in the molecule, such as polyvinyl alcohol resins, ethylene-vinyl alcohol copolymer resins, and butenediol-vinyl alcohol copolymer resins, are preferred because they have excellent gas barrier properties and therefore are likely to prevent the adhesive layer components from migrating to the conductive layer even when used as a thin film layer.

[0048] Examples of the polyvinyl alcohol resin include "Exceval" (registered trademark) manufactured by Kuraray Co., Ltd., "Gosenol" (registered trademark) manufactured by Mitsubishi Chemical Corporation, and "Denka Poval" (registered trademark) manufactured by Denka Co., Ltd. Examples of the ethylene-vinyl alcohol copolymer resin include "Eval" (registered trademark) manufactured by Kuraray Co., Ltd., "STRADER" (registered trademark) and "Exevia" (registered trademark) manufactured by Sumitomo Chemical Co., Ltd., and "Soarnol" (registered trademark) manufactured by Mitsubishi Chemical Corporation. Examples of the butenediol-vinyl alcohol copolymer resin include "Nichigo G-Polymer" (registered trademark) manufactured by Mitsubishi Chemical Corporation.

[0049] In addition, when the resin material of the migration prevention layer is a polymeric compound having a highly polar functional group such as a hydroxyl group, particularly when the resin material of the migration prevention layer is a polyvinyl alcohol resin, an ethylene-vinyl alcohol copolymer resin, or a butenediol-vinyl alcohol copolymer resin, the flame retardant of the adhesive layer is preferably a phosphorus-containing compound, and more preferably, two or more phosphorus-containing compounds are used. In this case, a conductive adhesive sheet having more effective flame retardancy can be realized by combining a flame-retardant adhesive layer and a migration prevention layer.

[0050] When the migration prevention layer is combined with the above-mentioned adhesive layer, as described above, the content of the phosphorus-containing compound in the adhesive layer (when two or more phosphorus-containing compounds are used, the total content thereof) is preferably 10 to 60 mass % and more preferably 20 to 50 mass % based on the total solid content. When the content is 10 mass % or more, the UL94VTM-2 standard of the UL94VTM flame retardancy standard can be satisfied, and sufficient flame retardancy can be ensured. When the content is 60 mass % or less, the adhesive strength and holding strength of the conductive adhesive sheet to the adherend can be ensured. That is, by setting the content in the range of 10 to 60 mass %, in addition to the excellent barrier property of the migration prevention layer, the compatibility of flame retardancy, adhesive strength, and holding strength can be effectively exhibited. When the content is 20 to 50 mass %, in addition to the excellent barrier property of the migration prevention layer, the compatibility of flame retardancy, adhesive strength, and holding strength can be even more effectively exhibited.

[0051] [Other ingredients] In order to impart properties such as gas barrier properties, adhesion, and coating strength to the resin material, a migration prevention layer may be formed by adding a filler having excellent barrier properties such as silica or alumina, or an epoxy-based or isocyanate-based curing agent to the resin material.

[0052] (Method of manufacturing conductive adhesive sheet) An embodiment of the method for producing a conductive adhesive sheet of the present application will be described. The method for producing a conductive adhesive sheet of the present embodiment can include a step of preparing a conductive layer-forming paint containing a conductive material, a binder, and a solvent, a step of forming a conductive layer on a substrate by applying the conductive layer-forming paint onto the substrate and drying it, a step of forming a migration prevention layer on the conductive layer, and a step of forming or arranging an adhesive layer on the migration prevention layer.

[0053] <Paint for forming conductive layer> The conductive layer-forming paint can be prepared by mixing a conductive material, a binder, and a solvent.

[0054] The conductive material may be at least one selected from the conductive polymer materials and carbon materials constituting the conductive layer described above, and the binder may be the same as the binder constituting the conductive layer described above.

[0055] The solvent preferably contains a protic polar solvent and an aprotic polar solvent. By using a protic polar solvent and an aprotic polar solvent in combination, the conductive layer can be formed at a relatively low drying temperature.

[0056] Examples of the protic polar solvent include water, ethyl alcohol, methyl alcohol, n-propyl alcohol, isopropyl alcohol, n-butyl alcohol, isobutyl alcohol, ethylene glycol, and propylene glycol. Examples of the aprotic polar solvent include dimethyl sulfoxide, N-methylpyrrolidone, N-ethylpyrrolidone, N,N-dimethylformamide, acetonitrile, acetone, and tetrahydrofuran.

[0057] The content of the solvent is not particularly limited, but may be from 50.0% by mass to 99.5% by mass based on the total mass of the coating material for forming the conductive layer.

[0058] <Formation of conductive layer> Examples of a method for applying the conductive layer-forming coating material onto a substrate include a bar coating method, a reverse coating method, a gravure coating method, a microgravure coating method, a die coating method, a dipping method, a spin coating method, a slit coating method, and a spray coating method.

[0059] The drying after the coating may be performed under conditions that allow the solvent component of the coating material for forming the conductive layer to evaporate, and is preferably performed at 100 to 150°C for 5 to 60 minutes. If the solvent remains in the conductive layer, the strength tends to be reduced. The drying method may be, for example, hot air drying, heat drying, vacuum drying, natural drying, etc. If necessary, the coating film may be irradiated with UV light or EB light to harden the coating film, thereby forming the conductive layer.

[0060] <Formation of migration prevention layer> To form a migration prevention layer on the conductive layer, the resin material constituting the migration prevention layer is dissolved in a protic polar solvent used in the conductive layer-forming paint to prepare a migration prevention layer-forming paint, and this migration prevention layer-forming paint is then applied onto the conductive layer and dried.

[0061] <Formation of adhesive layer> To form an adhesive layer on the migration prevention layer, for example, a coating material for forming an adhesive layer containing the above-mentioned adhesive, flame retardant, and solvent may be applied and dried. The method of applying the coating material for forming an adhesive layer on the migration prevention layer and drying it is not particularly limited, and various coating devices and drying devices can be used. In addition, the solvent is not particularly limited, and it is sufficient if it can mix the adhesive and the flame retardant.

[0062] In addition, to place an adhesive layer on the migration prevention layer, an adhesive layer can be formed separately on a release film using the adhesive layer-forming paint, and this separately formed adhesive layer can be placed on the migration prevention layer by, for example, attaching it thereto. EXAMPLES

[0063] The present application will be described in detail below using examples. However, the present application is not limited to the following examples. Unless otherwise specified, in the following, "parts" means "parts by mass".

[0064] Example 1 <Preparation of paint for forming conductive layer> The following components were added and mixed to prepare a conductive layer forming paint a1. (1) Polythiophene-based conductive polymer dispersion (manufactured by Soken Chemical Industries, Ltd., product name "Verasol WED-SM", conductive polymer: PEDOT-PSS, solid content concentration: 1.5 mass%, solvent: water): 55.0 parts (2) Binder solution (water-soluble polyester resin solution, manufactured by GOO Chemical Co., Ltd., product name "Pluscoat Z-565", solid content concentration: 25.0 mass%, solvent: water): 10.0 parts (3) Solvent (dimethyl sulfoxide): 5.0 parts (4) Solvent (n-propyl alcohol): 20.0 parts (5) Pure water: 10.0 parts

[0065] <Formation of conductive layer> Next, 130 μm thick aramid paper containing a flame retardant material (manufactured by Teijin DuPont Advanced Paper Co., Ltd., product name "Nomex 410") was used as a substrate, and the conductive layer forming paint a1 was applied to one main surface of the substrate using a bar coater, and then dried at 110° C. for 3 minutes. This produced a conductive sheet with a conductive layer formed on one main surface. The conductive layer had a thickness of 1.0 μm.

[0066] <Preparation of paint for forming migration prevention layer> The following components were added and mixed to prepare paint b1 for forming a migration prevention layer. (1) Butenediol-vinyl alcohol copolymer resin (manufactured by Mitsubishi Chemical Corporation, product name “Nichigo G-Polymer BVE8049Q”): 4.0 parts (2) Solvent (ethanol): 26.0 parts (3) Pure water: 70.0 parts

[0067] <Formation of migration prevention layer> Next, the paint b1 for forming the migration prevention layer was applied to the conductive layer side of the conductive sheet prepared previously using a bar coater, and then dried at 100°C for 3 minutes. This produced a conductive sheet with a migration prevention layer, in which a conductive layer and a migration prevention layer were laminated on one main surface. The thickness of the migration prevention layer was 0.5 μm.

[0068] <Preparation of paint for forming adhesive layer> The following components were added and mixed to prepare adhesive layer forming paint c1. (1) Acid-free resin adhesive (manufactured by Daido Chemical Industry Co., Ltd., product name "Dicalac 5021", solid content concentration: 30.0 mass%, solvent: ethyl acetate): 58.3 parts (2) Isocyanate-based crosslinking agent (manufactured by Tosoh Corporation, product name “Coronate HX”, solid content concentration: 100.0% by mass): 0.1 part (3) Tackifier (terpene resin, manufactured by Yasuhara Chemical Co., Ltd., trade name “YS Polystar K125”): 3.5 parts (4) Flame retardant (phosphate ester, manufactured by Daihachi Chemical Industry Co., Ltd., product name “CR-741”): 7.0 parts (5) Flame retardant (ammonium polyphosphate, manufactured by Budenheim, product name “TERRAJU C-30”): 7.0 parts (6) Solvent (ethyl acetate): 24.1 parts

[0069] <Formation of conductive adhesive sheet> The above-mentioned adhesive layer forming paint c1 was applied to the release-treated surface of a 50 μm thick release film (manufactured by Nippa Corporation, product name "J0-L") which had been release-treated on one side of a PET film, and dried at 80°C for 5 minutes to form a 30 μm thick adhesive layer on the release film.

[0070] Next, the adhesive layer of the release film was superimposed on the migration prevention layer side of the conductive sheet with migration prevention layer prepared previously, pressed with a 2 kg rubber roller, and aged for 48 hours in an atmosphere of 40°C to produce a conductive adhesive sheet with the release film attached, and the portion without the release film was used as the conductive adhesive sheet of Example 1.

[0071] Example 2 The conductive adhesive sheet of Example 2 was prepared in the same manner as Example 1, except that a 50 μm thick aramid paper containing a flame-retardant material (manufactured by Teijin DuPont Advanced Papers, product name "Nomex 410") was used as the base material.

[0072] Example 3 A conductive adhesive sheet of Example 3 was produced in the same manner as in Example 1, except that the thickness of the conductive layer was 0.6 μm.

[0073] Example 4 A conductive adhesive sheet of Example 4 was produced in the same manner as in Example 1, except that the thickness of the migration prevention layer was set to 0.1 μm.

[0074] Example 5 A conductive adhesive sheet of Example 5 was produced in the same manner as in Example 1, except that the thickness of the adhesive layer was 10 μm.

[0075] Example 6 <Preparation of paint for forming migration prevention layer> The following components were added and mixed to prepare paint b2 for forming a migration prevention layer. (1) Ethylene-vinyl alcohol copolymer resin (manufactured by Sumitomo Chemical Co., Ltd., product name “NOH3000”, solid content concentration: 6.0% by mass, solvent: water): 66.6 parts (2) Solvent (ethanol): 20.0 parts (3) Pure water: 13.4 parts

[0076] Next, the conductive adhesive sheet of Example 6 was prepared in the same manner as Example 1, except that the migration prevention layer-forming paint b2 was used instead of the migration prevention layer-forming paint b1 of Example 1 to form a migration prevention layer having a thickness of 1.0 μm.

[0077] Example 7 <Preparation of paint for forming adhesive layer> The following components were added and mixed to prepare adhesive layer forming paint c2. (1) Acid-free resin adhesive (manufactured by Daido Chemical Industry Co., Ltd., product name "Dicalac 5021", solid content concentration: 30.0 mass%, solvent: ethyl acetate): 60.9 parts (2) Isocyanate-based crosslinking agent (manufactured by Tosoh Corporation, product name “Coronate HX”, solid content concentration: 100.0% by mass): 0.1 part (3) Tackifier (terpene resin, manufactured by Yasuhara Chemical Co., Ltd., trade name “YS Polystar K125”): 9.0 parts (4) Flame retardant (phosphate ester, manufactured by Daihachi Chemical Industry Co., Ltd., product name “CR-741”): 5.0 parts (5) Solvent (ethyl acetate): 25.0 parts

[0078] Next, the conductive adhesive sheet of Example 7 was prepared in the same manner as Example 1, except that the adhesive layer-forming paint c2 was used instead of the adhesive layer-forming paint c1 of Example 1 to form an adhesive layer having a thickness of 25 μm.

[0079] Example 8 <Preparation of paint for forming adhesive layer> The following components were added and mixed to prepare adhesive layer forming paint c3. (1) Acid-free resin adhesive (manufactured by Daido Chemical Industry Co., Ltd., product name "Dicalac 5021", solid content concentration: 30.0 mass%, solvent: ethyl acetate): 68.3 parts (2) Isocyanate-based crosslinking agent (manufactured by Tosoh Corporation, product name “Coronate HX”, solid content concentration: 100.0% by mass): 0.1 part (3) Tackifier (terpene resin, manufactured by Yasuhara Chemical Co., Ltd., trade name “YS Polystar K125”): 4.5 parts (4) Flame retardant (phosphate ester, manufactured by Daihachi Chemical Industry Co., Ltd., product name “CR-741”): 2.0 parts (5) Flame retardant (ammonium polyphosphate, manufactured by Budenheim, product name “TERRAJU C-30”): 1.0 part (6) Solvent (ethyl acetate): 24.1 parts

[0080] Next, the conductive adhesive sheet of Example 8 was prepared in the same manner as Example 1, except that the adhesive layer-forming paint c3 was used instead of the adhesive layer-forming paint c1 of Example 1 to form an adhesive layer having a thickness of 25 μm.

[0081] Example 9 The conductive adhesive sheet of Example 9 was produced in the same manner as in Example 1, except that a 100 μm thick flame retardant-containing polycarbonate sheet (manufactured by Sumitomo Bakelite Co., Ltd., product name "PHF860MAB") was used as the substrate.

[0082] Example 10 The conductive adhesive sheet of Example 10 was produced in the same manner as in Example 1, except that the thickness of the migration prevention layer was 0.06 μm.

[0083] Example 11 <Preparation of paint for forming migration prevention layer> The following components were added and mixed to prepare paint b3 for forming a migration prevention layer. (1) Methacrylic copolymer resin (manufactured by Mitsubishi Chemical Corporation, product name “Dianal BR-113”): 4 parts (2) Solvent (methyl ethyl ketone): 96.0 parts

[0084] Next, the conductive adhesive sheet of Example 11 was prepared in the same manner as Example 1, except that the migration prevention layer-forming paint b3 was used instead of the migration prevention layer-forming paint b1 of Example 1, and a migration prevention layer having a thickness of 0.5 μm was formed.

[0085] Comparative Example 1 The conductive adhesive sheet of Comparative Example 1 was prepared in the same manner as Example 1, except that a 100 μm thick PET film (manufactured by Toyobo Co., Ltd., product name "A4300") was used as the substrate and that a substrate not containing a flame-retardant material was used.

[0086] Comparative Example 2 A conductive adhesive sheet of Comparative Example 2 was produced in the same manner as in Example 1, except that no migration prevention layer was formed.

[0087] Comparative Example 3 <Preparation of paint for forming adhesive layer> The following components were added and mixed to prepare adhesive layer forming paint C4 that does not contain flame retardants. (1) Acid-free resin adhesive (manufactured by Daido Chemical Industry Co., Ltd., product name "Dicalac 5021", solid content concentration: 32.0 mass%, solvent: ethyl acetate): 68.3 parts (2) Isocyanate-based crosslinking agent (manufactured by Tosoh Corporation, product name “Coronate HX”, solid content concentration: 100.0% by mass): 0.1 part (3) Tackifier (terpene resin, manufactured by Yasuhara Chemical Co., Ltd., trade name “YS Polystar K125”): 5.5 parts (4) Solvent (ethyl acetate): 24.1 parts

[0088] Next, a conductive adhesive sheet of Comparative Example 3 was prepared in the same manner as in Example 1, except that the adhesive layer-forming paint c4 was used instead of the adhesive layer-forming paint c1 of Example 1 to form an adhesive layer having a thickness of 25 μm.

[0089] Comparative Example 4 A conductive adhesive sheet of Comparative Example 4 was produced in the same manner as in Example 1, except that the thickness of the conductive layer was 0.4 μm.

[0090] Comparative Example 5 After removing the release film from the conductive adhesive sheet with release film prepared in Example 1, an aluminum foil composite film (manufactured by PANAC Corporation, product name "Alpet", product number "10-75", thickness: 85 μm) was bonded to the exposed adhesive layer.

[0091] Next, the adhesive layer forming paint c1 prepared in Example 1 was applied to the release-treated surface of a 50 μm thick release film (manufactured by Nippa Corporation, product name "J0-L") which had been release-treated on one side of a PET film, and dried at 80°C for 5 minutes to form an adhesive layer 25 μm thick on the release film.

[0092] Next, the adhesive layer of the release film was superimposed on the aluminum foil composite film side of the conductive sheet with aluminum foil composite film prepared earlier, pressed with a 2 kg rubber roller, and aged for 48 hours in an atmosphere at 40°C to produce a conductive adhesive sheet with the release film attached, and the portion without the release film was used as the conductive adhesive sheet of Comparative Example 5.

[0093] The conductive adhesive sheets of Examples 1 to 11 and Comparative Examples 1 to 5 were evaluated as follows.

[0094] <Total thickness measurement> After the release film was peeled off from the prepared conductive adhesive sheet with a release film, the total thickness of the conductive adhesive sheet was measured with a dial gauge.

[0095] <Measurement of surface electrical resistance> The conductive adhesive sheet with release film thus prepared was cut into a 50 mm square, the release film was then peeled off, and the adhesive layer side of the conductive adhesive sheet was pressed against an alkali-free glass manufactured by Corning Incorporated (product name "Eagle XG", thickness: 0.7 μm) to prepare a measurement sample.

[0096] Next, the surface electrical resistance value of the measurement sample was measured using a high-frequency eddy current non-destructive resistivity measuring device (product name "EC-80P") manufactured by Napson Corporation. Specifically, the probe of the resistivity measuring device was placed on the substrate side of the measurement sample, and the surface electrical resistance value of the substrate side was measured. This surface electrical resistance value of the substrate side was taken as the surface electrical resistance value of the conductive adhesive sheet. The measured surface electrical resistance value was then evaluated as follows. Evaluation A: When the surface electrical resistance is 50 to 120 Ω / square Evaluation B: When the surface electrical resistance is 121 to 200 Ω / square Evaluation C: Surface electrical resistance is 201Ω / square or more

[0097] <Adhesive strength> The conductive adhesive sheet with release film thus prepared was cut to a width of 25 mm and a length of 150 mm, after which the release film was peeled off and the sheet was attached to a stainless steel plate (SUS304), and pressure-bonded using a roller weighing 2 kg, which was moved back and forth once at a speed of 5 mm / sec. The time from bonding to the measurement of adhesive strength was set to 24 to 36 hours, and the adhesive strength was measured by peeling the sheet in a 180° direction at a speed of 5 mm / sec using a tensile tester. The measurement was carried out indoors at 23±3°C.

[0098] <Flame retardancy> A thin material vertical flame test (ASTM D4804) was conducted based on the UL94VTM flame retardancy standard. Specifically, the conductive adhesive sheet with release film was cut into a length of 200 mm and a width of 50 mm, the release film was removed, rolled into a cylindrical shape, and attached vertically to a clamp. A 20mm flame was applied twice for 3 seconds, and the flame behavior was judged as VTM-0, VTM-1, VTM-2, or Not.

[0099] <Long-term reliability> The conductive adhesive sheet with the release film thus prepared was cut into 50 mm squares, the release film was peeled off, and the adhesive layer side of the conductive adhesive sheet was pressed against Corning's alkali-free glass (product name "Eagle XG", thickness: 0.7 μm) to obtain a sample for evaluating long-term reliability. This evaluation sample was stored for 1000 hours in a thermo-hygrostat at a temperature of 65° C. and a humidity of 95%, and the rate of increase in surface electrical resistance before and after storage was measured. Next, the long-term reliability of the conductive adhesive sheet was evaluated as follows. Grade A: The increase in surface electrical resistance is less than 20% and the surface electrical resistance after storage is less than 200 Ω / square Evaluation B: When the increase in surface electrical resistance is less than 30% and the surface electrical resistance after storage is less than 200 Ω / square Grade C: When the increase in surface electrical resistance is 30% or more, or when the surface electrical resistance after storage is 200 Ω / square or more

[0100] The above results are shown in Tables 1 and 2 together with the configuration of the conductive adhesive sheets produced.

[0101] [Table 1]

[0102] [Table 2]

[0103] As seen from Tables 1 and 2, the conductive adhesive sheets of Examples 1 to 9 obtained good results in terms of surface electrical resistance, adhesive strength, flame retardancy, and long-term reliability. The conductive adhesive sheets of Examples 10 and 11 obtained good results in terms of surface electrical resistance, adhesive strength, and flame retardancy, but Example 10, in which the thickness of the migration prevention layer was less than 0.1 μm, and Example 11, in which the resin constituting the migration prevention layer did not contain a hydroxyl group, each showed a tendency toward decreased long-term reliability.

[0104] On the other hand, in Comparative Example 1, which did not use a flame-retardant base material, the flame retardancy was reduced, in Comparative Example 2, which did not form a migration prevention layer, the long-term reliability was reduced, in Comparative Example 3, which did not contain a flame retardant in the adhesive layer, the flame retardancy was reduced, in Comparative Example 4, in which the conductive layer was thinner than 0.5 μm, the surface electrical resistance value exceeded 200 Ω / square and the long-term reliability was also reduced, and in Comparative Example 5, in which a metal layer was disposed, the surface resistance value was below the measurement limit value and could not be measured, and similarly, the long-term reliability was also impossible to measure.

[0105] The present application can be implemented in other forms than those described above. The embodiments disclosed in the present application are merely examples and are not limited thereto. The scope of the present application shall be interpreted in accordance with the appended claims rather than the above description of the specification, and all modifications within the scope of the claims are intended to be included in the scope of the claims. [Explanation of symbols]

[0106] 10 Conductive adhesive sheet 11 Base material 12 Conductive layer 13 Migration prevention layer 14 Adhesive layer

Claims

1. A conductive adhesive sheet including, in this order, a substrate, a conductive layer, a migration prevention layer, and an adhesive layer, The substrate is made of a flame retardant material; the conductive layer includes a conductive material and a binder; the conductive material includes at least one selected from a conductive polymer material and a carbon material, The migration prevention layer is made of a resin material, The adhesive layer includes an adhesive and a flame retardant, the surface electrical resistance value of the substrate side is 50 to 200 Ω / square, A conductive adhesive sheet having a total thickness of 50 to 200 μm.

2. The conductive adhesive sheet according to claim 1, wherein the thickness of the substrate is 25 to 180 μm.

3. The conductive adhesive sheet according to claim 1, wherein the conductive layer has a thickness of 0.5 to 2.0 μm.

4. The conductive adhesive sheet according to claim 1, wherein the migration prevention layer has a thickness of 0.1 to 2.0 μm.

5. The conductive adhesive sheet according to claim 1 , wherein the resin material of the migration prevention layer is a polymer compound containing a hydroxyl group.

6. 6. The conductive adhesive sheet according to claim 5, wherein the polymer compound containing a hydroxyl group is polyvinyl alcohol, an ethylene-vinyl alcohol copolymer, or a butenediol-vinyl alcohol copolymer.

7. The conductive adhesive sheet according to claim 1 , wherein the flame retardant in the adhesive layer comprises a phosphorus-containing compound.

8. The conductive adhesive sheet according to claim 1 , wherein the flame retardant in the adhesive layer contains two or more types of phosphorus-containing compounds.

9. the resin material of the migration prevention layer is a polymer compound containing a hydroxyl group, The conductive adhesive sheet according to claim 1 , wherein the flame retardant in the adhesive layer comprises a phosphorus-containing compound.

10. the resin material of the migration prevention layer is a polymer compound containing a hydroxyl group, The conductive adhesive sheet according to claim 1 , wherein the flame retardant in the adhesive layer contains two or more types of phosphorus-containing compounds.

11. the resin material of the migration prevention layer is a polymer compound containing a hydroxyl group, the polymer compound containing a hydroxyl group is polyvinyl alcohol, an ethylene-vinyl alcohol copolymer, or a butenediol-vinyl alcohol copolymer; The conductive adhesive sheet according to claim 1 , wherein the flame retardant in the adhesive layer comprises a phosphorus-containing compound.

12. The conductive adhesive sheet according to any one of claims 7 to 11, wherein the content of the phosphorus-containing compound in the adhesive layer is 10 to 60 mass %.

Citation Information

Patent Citations

  • Radio wave absorber, and laminate thereof

    JP2006120836A

  • Transparent conductive adhesive sheet

    JP2017054734A